Area Industri Gamping sebagai Faktor Risiko Gangguan Fungsi Paru - A A Subijanto (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: Chronic Obstructive Pulmonary Disease is one the major public health problems in Indonesia. National data in 1992 described that bronchitis and asma was situated at the seventh rank among 10 leading fatal diseases. One of their risk factors is exposure of dust which is produced by industry including chalkpowder industry. In Indonesian country, there were some active chalkpowder industy in the area.Objective: This research was aimed to investigate whether distance between home and chalk powder industry is a risk factor for poor lung function.Material and Method: The study population was men who stayed in nearby the chalk powder industry during at least last 5 years, smoke, and were not employee in the chalkpowder industry. The study design was cross- sectional survey. Sampling method was quota sampling. Lung function was examined by respirometer to measure Vital Capacity (VC) and Forced Expiratory Volume One Second (FEV-1).Results: The findings of this study reveals that distance of home to chalk powder industry is a risk factor to prevalence of obstructive and restrictive lung. The risk of residents living in the radius of less than 500 meter from the industry is 9.75 higher to obstructive lung than residents living within the radius of 500 to 100 meter from the industry. In addition, the risk to suffer restrictive lung is 1.38 higher in residents living within the radius of less than 500 meters from the industry.Keywords: chalkpowder, risk factor, COPD